ENTRANCE OF HOT PYROCLASTIC FLOWS INTO THE SEA: EXPERIMENTAL OBSERVATIONS - Freundt A. (My University, 2003)
The entrance of hot pyroclastic flows into water has been observed in a series of experiments in which shooting granular flows of hot ignimbrite ash (≤403 °C), of bulk density near that of water, run down a smooth chute and enter a water-filled tank at an angle of 26°. Flows of relatively cool ash (<150°C)) impulsively displace some volume of near-shore water upon impact, generating a wave that rapidly travels away from shore. the granular flow material then separates into two portions. (1) fine-ash surge cloud is formed where hits and down-tank over water. (2) main portion penetrates surface mixes with water, creating turbulent mixing zone resembling hydraulic jump, which advances downstream as long pyroclastic maintained. most pumice floats to surface, lithics coarse ash fall out onto floor, but remains in suspension forms turbidity current down floor tank. increasing temperature, an fraction incoming initially transported along surface; almost all takes this path at temperatures>250°C. Mixing across the water surface over some distance from shore generates steam explosions forming fountains of wet and dry ash and convectively rising fine-ash plumes. Steam explosions increase in strength and lateral extent towards higher ash temperatures and mass fluxes. The explosions generate water waves that remain driven by massive fountain fallout across some distance from shore. The ash fountains feed pyroclastic surges, which advance down tank over water at high speeds. Underwater plumes of sediment falling from the ash fountains and surges drop coarse load onto the floor whereas the finer load forms a turbidity current. High temperature and poor size sorting of pyroclastic flows are key parameters that determine the processes of interaction with water and the associated hazards. Poor sorting allows for the formation of ash-cloud surges moving over water, even from cool flows. High temperatures cause littoral explosions and facilitate extensive mass transport over water. All flows generate tsunami waves by different mechanisms. Electronic supplementary material (two movies) is available if you access this article at http://dx.doi.org/10.1007/s00445-002-0250-1. On that page (frame on the left side), a link takes you directly to the supplementary material.
Keywords: ASH-CLOUD SURGE; HOT ASH-WATER MIXING; LITTORAL EXPLOSION; PYROCLASTIC FLOW; TSUNAMI; TURBIDITY CURRENT